Princípios do desenho universal para aprendizagem, nos objetos do conhecimento de geografia, para alunos do 4º ano do ensino fundamental I - Diório, Raquel (2020)
This research aimed to investigate strategies for the curriculum of objects of geography knowledge, aimed at regularly enrolled students and the inclusion ones with autism spectrum disorder, ASD, who attend the 4th grade of teaching Elementary School I, thus seeking to assist teachers who live with the reality of inclusion and its implications in learning. For this investigation, the principles of Universal Design for Learning (DUA), enabling the organization of knowledge in order to promote learning that ensures the reach of all within an egalitarian environment. Varied pedagogical practices were selected and they proposed different means for the presentation of an object of knowledge, since the intention was not curriculum adaptation. The selected knowledge objects are in agreement with the national common curricular basis, BNCC, approved on december 20th, 2017. The games and apps used are in public domain, available and accessible on the Internet. Students authorized to participate in the research summed 50 and were organized in two 4th grade classes of elementary school I, between 9 and 10 year-olds, regularly enrolled in a traditional private school chain, in the capital of São Paulo. After the selection of knowledge objects and the attribution of strategies, the classes were taught by the researcher in both ones, during the period of 3 months, in the second semester of the school year. It was possible to record academic advances of students in both classes, with the exception of the inclusion student with ASD. It is also recorded that the activities performed were used as a means of evaluation by the school, after validation by their pedagogical guidance that considered them relevant and effective, scoring that the variation of strategies actually promoted a better acquisition of the expected skills for each object of knowledge and that they were performed in a procedural manner.